PENGARUH GAYA KEPEMIMPINAN DAN DISIPLIN KERJA TERHADAP KINERJA PEGAWAI PADA DIREKTORAT KEPOLISIAN UDARA CABANG KOTA TANGERANG SELATAN - Muhammad Mirsa; R.A. Kadarmanta (CV. KAMPUS AKADEMIK PUBLISHING, 2025)
The purpose of this study is to determine the simultaneous influence of leadership style and work discipline on the performance of employees of the South Tangerang Branch of the Air Police Directorate. This study uses quantitative research. With a research population of 646 people and 86 people as samples taken using the Slovin formula in this study. Data analysis techniques used are descriptive statistical analysis, data instrument testing, classical assumption testing, quantitative analysis, and hypothesis testing. The results of the study show that the results of the hypothesis test (t test) of the leadership style variable (X1) on employee performance (Y) obtained a calculated t value > t table or (16.843 > 1.989). Thus, H0 is rejected and H1 is accepted, this shows that the results of the study show that there is a significant influence of leadership style on employee performance. The multiple linear regression equation Y = 0.179 + 0.360 X1 + 0.445 X2 means that employee performance even without the influence of leadership style and work discipline already has an influence of 0.179. Simultaneously, leadership style and work discipline have a positive and significant effect on employee performance, this is proven by the calculated F value > F table, which is (264.977 > 3.113) with a significance value of 0.05 (0.000 < 0.05), so Ho is rejected and H3 is accepted, meaning that there is a positive and significant effect between leadership style and work discipline on employee performance simultaneously at the South Tangerang Branch of the Air Police Directorate.